A STUDY OF PSYCHOSOCIAL FACTORS RELATED TO APPROPRIATE WEIGHT-LOSS BEHAVIORS OF ADOLESCENTS - สถิรนันท์, สิรภัทร; สิทธิ์ศิรอรรถ , ฉัฐวีณ์; แสนแจ่มใส, สุพัทธ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2021)
The objectives of this study were as follows (1) to examine the relationship between the psychological factors concerned ego identity and locus of control, social and situation factors including role models and media exposure, and psychological stage factors, such as attitudes to weight-loss and body image satisfaction related to weight-loss behaviors, (2) to predict to weight-loss behaviors using the psychological factor, social situation factors, and psychological stage factors. The participants were in late adolescence, consisting of 360 undergraduate students. via the stratified random sampling method. The statistics for analysis included mean, standard deviation, Pearson’s product moment correlation coefficient, and both enter and stepwise multiple regression analysis. the results of, the study were as follows. 1. Ego identity, role model, media exposure and body image satisfaction correlated positively to the appropriate weight-loss behaviors (**p > .01). The locus of control factor correlated positively with appropriate weight-loss behaviors (*p > .05). 2. The factors of ego identity, locus of control, role model, media exposure, weight-loss attitudes, and body image satisfaction in combination can predict appropriate weight-loss behaviors at 33.9% and a combination prediction of appropriate weight-loss behaviors terms of consumption at 25.6% and exercise at 26.4%. appropriate Weight-loss behaviors, consumption, and exercise as the strongest predictor of media exposure, ego identity, locus of control and attitudes to weight-loss respectively.